KONTRIBUSI PEMUDA DALAM PEMBANGUNAN SOSIAL DAN INOVASI - Cecep Hilman; Arnadi (Prosiding Seminar Nasional Indonesia, 2025)
Youth contribution to social development and innovation is the active engagement and constructive participation of young people (generally aged 15-30 years) in eflorts to improve the quality of life in society and create creative solutions to social challenges. This includes the role of youth in developing new ideas, applying technology, leading social initiatives, and engaging in decision-making processes that impact society. These contributions can take many forms, including social entrepreneurship, environmental activism, technology development, volunteering, and public policy advocacy. Through this engagement, youth not only contribute to current development but also shape the future of society by bringing fresh perspectives, energy, and innovation in addressing social, economic, and environmental issues. The study in this research uses the literature method. The results show that youth have the potential to drive innovation and positive social change. The creativity, digital skills and fresh perspectives brought by the younger generation have contributed to innovative solutions to various social and environmental challenges. However, the research also identified several barriers, such as limited access to resources and lack of platforms for meaningful participation. Therefore, to maximise the contribution of youth, supportive policies and investments in their capacity development are needed.